The Influence of Work Environment, Work Discipline, and Job Satisfaction on Employee Performance at the Representative Office of the National Population and Family Planning Agency (BKKBN) Sumatra Utara - Pohan, Mukmin; Rialdy, Novien; Mirandani, Delva Nizar (Journal of International Conference Proceedings, 2023)
The purpose of this study is to investigate the relationship between working environment, work discipline, and job satisfaction and employee performance in representative offices of the National Population and Family Planning Agency of North Sumatra (BKKBN). A quantitative study and an associative approach were used in this study. The sample for this study was drawn from all full-time employees of the National Population and Family Planning Board (BKKBN) Representative Office in North Sumatra Province, a total of 84 persons. Data collection techniques used in media interviews (interviews), research documents, and surveys (surveys). The data analysis techniques used in this study used classical hypothesis testing, multiple linear regression and hypothesis testing. The results of this study suggest that work environment has a positive but not significant impact on employee performance. Morale had a positive impact on employee productivity, but the impact was small. On the one hand, job satisfaction has a positive and significant impact on employee productivity.